Contact allergy in the population of patients with chronic inflammatory dermatoses and contact hypersensitivity to corticosteroids - Kot, Marek; Bogaczewicz, Jaroslaw; Kręcisz, Beata; Woźniacka, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction : Clinical studies indicate that contact allergy to glucocorticosteroids (GCS) is not rare and has been increasingly reported over the past decade. Among the risk factors for developing contact hypersensitivity to topical corticosteroids, chronic inflammatory skin diseases and polyvalent contact allergy seem to be most important. Aim : To present the structure of contact allergy in the population of patients with chronic inflammatory dermatoses (CID) and contact hypersensitivity to corticosteroids. Material and methods : Twenty-seven patients with contact allergy to GCS and chronic inflammatory dermatoses were patch tested with 28 European Baseline Series allergens and 8 corticosteroid allergens. This study group consisted of 5 patients with atopic dermatitis (AD), 15 patients with contact eczema (CE) and 7 with chronic leg eczema (CLE). Nineteen (70.4%) patients were females and 8 (29.6%) were males. Results : In the study group, the most sensitizing non-steroidal allergens were nickel sulfate (51.8%), cobalt chloride (33.3%) and balsam of Peru (29.6%). The most sensitizing corticosteroid allergens were budesonide (77.8%), betamethasone valerate and clobetasol propionate (55.5% each). A total of 77.8% of patients allergic to GCS also showed sensitivity to at least one non-steroidal allergen from the European Baseline Series. Conclusions : The most important risk factors for developing contact allergy to corticosteroids appear to be chronic inflammatory dermatoses, long disease duration, extended on-and-off topical corticosteroid use, patients presenting two or more positive patch test results and polyvalent contact allergy to metal salts and to other non-steroidal haptens.